2019
DOI: 10.1007/s00167-019-05596-y
|View full text |Cite
|
Sign up to set email alerts
|

Distal tuberosity osteotomy in open-wedge high tibial osteotomy does not exacerbate patellofemoral osteoarthritis on arthroscopic evaluation

Abstract: Purpose The purpose of the present study was to use arthroscopy to evaluate the effect of distal tuberosity osteotomy (DTO) in open‐wedge high tibial osteotomy (OW‐HTO) on patellofemoral (PF) cartilage degradation. Methods Between 2012 and 2017, 46 knees underwent DTO in OW‐HTO, and 65 knees underwent conventional OW‐HTO (cOW‐HTO). To assess changes in patellar height, the Blackburne–Peel (BP) ratio and the Caton–Deschamps (CD) index were measured. Arthroscopic evaluation on the PF joint was performed at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…Using this method of maintaining patellar height, Horikawa et al. [ 63 ] reported that patellar height was almost the same preoperatively and postoperatively.…”
Section: Other Considerations In Preoperative Planningmentioning
confidence: 99%
“…Using this method of maintaining patellar height, Horikawa et al. [ 63 ] reported that patellar height was almost the same preoperatively and postoperatively.…”
Section: Other Considerations In Preoperative Planningmentioning
confidence: 99%
“…5,7 The superiority of Gaasbeek et al's technique with DTO, as compared with PTO, has been reported. [5][6][7][8][9][10][11][12][13] However, since it is sometimes difficult to set the DTO line perpendicular to the OWHTO line due to the triangular shape of the proximal tibia, we The main advantage of this guide is the ability to accurately set the second osteotomy line perpendicular to the first, thereby preventing gap formation at the second osteotomy site (Fig 9A). If the angle between the first and second osteotomy lines is obtuse, a gap will form ( Fig 9B).…”
Section: Discussionmentioning
confidence: 99%
“…Since the inception of this new technique, many authors have pointed out that patella height was not altered as compared with the conventional procedure. [5][6][7][8][9][10][11][12][13] In addition, Stoffel et al 14 experimentally revealed that OWHTO with DTO maintained normal patellofemoral joint biomechanics with no significant increase in patellofemoral cartilage pressure. However, setting the DTO (the second osteotomy) line perpendicular to the OWHTO (the first osteotomy) line, which prevents creating a gap at the DTO site, is quite difficult during the actual procedure due to the triangular shape of the proximal tibia.…”
mentioning
confidence: 99%
“…The effects of other factors on clinical outcomes should also be carefully considered in sagittal and axial view; Posterior tibial slope and patellofemoral OA might be associated with flexion contracture and poor clinical outcome after HTO [ 16 ]. Uni-compartment arthroplasty (UKA) and other types of HTO, such as hybrid HTO or opening-wedge distal tubercle osteotomy [ 6 , 17 ], might be considered for patients with symptoms of medial compartment OA who have a pelvic retroversion.…”
Section: Discussionmentioning
confidence: 99%